Islamic studies in Malaysian universities: a review and prospect - Md. Noon, Hazizan (Centre for Civilisational Dialogue, University of Malaysa, 2013)
This work raises a number of concerns and developments pertaining to the topic in expectation of a realistic strategy in making 'Islamic studies' in Malaysia more relevant to the current and future realities. To begin with, it stresses the point that, it is always useful for a discussion of any issue related to Islam to consider not only the ideal and permanent nature of Islam as a comprehensive Divine religion for mankind, but also its 'diverse manifestations' in history and in different socio-cultural contexts. This is due to the fact that the actual implementation of Islam, in particular its 'social teachings', in the past and present Muslim societies do not necessarily present uniformity despite their shared general religious principles. This is to be kept in mind if one is to be realistic and rational in perceiving the interplay between religious ideals and their translation into actual practice. The discussion centres around the experiences of International Islamic University Malaysia especially its Kulliyyah of Islamic Revealed Knowledge and Human Sciences in addressing the emerging contemporary challenges.It identified challenges facing Islamic studies in contemporary Malaysia and outlines IIUM strategies in responding to these challenges.